FAKTOR-FAKTOR YANG MEMENGARUHI RETURN ON ASSET - Katherine Kusuma Keegan; Sofia Prima Dewi (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
The purpose of this research is proving empirically the effect of Debt to Asset Ratio,Asset Tangibility, Asset Turnover, and Sales Growth on Return on Asset inmanufacturing companies listed on the Indonesia Stock Exchange during 2016-2019.Sample was selected using purposive sampling method and the valid data is 35manufacturing companies from a total population of 134 manufacturing companieslisted on the Indonesia Stock Exchange during 2016-2019. The data processingtechnique using multiple regression analysis with the EVIews 10 program andMicrosoft Excel 2013. The results showed Debt to Asset Ratio has a negative effect onReturn on Asset, Asset Tangibility has no negative effect on Return on Asset, AssetTurnover has no positive effect on Return on Asset, and Sales Growth has a positiveeffect on Return on Asset. The implication of this research is the need to improve thecompany's financial performance to increase the company's Return on Asset which will provide a good signal for investors.